Effect of some Nano fertilizers on growth and productivity of Broad Bean Vicia faba L. - علي, ثراء; رياض زيدان ,; رياض زيدان ,; جنان عثمان, (Latakia University Journal -Biological Sciences Series, 2024)
The research was conducted in Tishreen university during the period of 2021/2022 and 2022/2023, to determine the effect of some of Nano fertilizers on growth and productivity of Broad Bean Vicia faba L. The study included four treatments (T1 control without spraying, T2 spraying with Diamond , T3 spraying with Crystal, T4 spraying with Obar fix), The completely randomized design was used with three replications. The results showed that Tretment 4 spraying with Obar fix gave the superior results with significant difference in the most of vegetative indicators: number of leaves and branches/plant, fresh and dry weight, leaf surface area and indicator,efficiency of photosynthesis, and percentage of fruit set. Crystal compound the highest value for yield of plant 1014.6 g/plant and total yield 3.46 kg/m2 , compared to the control 6.46g/plant and 2.14 kg/m2. S.S.T (7.833%), and the least nitrate in pods (73 mlg/kg). There isn’t any significant difference between the treatments in the content of dry meter, carbohydrate and protein. Whereas, Crystal gave the superior results with significant difference in S.S.T (8.96%), and Obar fix compound the least value for content nitrate in pods (74 mlg/kg). Keywords[1]:Broad bean, Nano fertilizer, Percentage of fruit set, Total yield.